Vaccine equity in COVID-19: a meta-narrative review - Borowicz,J; Zhang,Z; Day,G; Pinto,da Costa M (BMJ Global Health, 2022)
The topic of inequitable vaccine distribution has been widely discussed by academics, journalists, and policy-makers in the context of the COVID-19 pandemic. However, research into perceptions of vaccine equity have been particularly neglected, resulting in a lack of universal understanding of vaccine equity.To address this, we conducted a meta-narrative review on COVID-19 vaccine equity according to the Realist And MEta-narrative Evidence Syntheses: Evolving Standards (RAMESES) publication standard. The review included articles published between January 2020 and September 2021. It aims to 1) identify research traditions that have considered this topic and investigate how it has been conceptualised; 2) explore any potential differences in understandings of the concept of vaccine equity adopted by distinct research groups; and 3) to investigate the angles from which authors based their recommendations on how vaccine equity can be achieved.Five meta-narratives from literature across various research traditions are identified, contextualised, and discussed: Frameworks and Mechanisms for Vaccine Allocation, Global Health Law, Vaccine Nationalism, Ethics and Morality, and Reparative Justice. Our findings indicate the need for a comparative review of existing global COVID-19 allocation frameworks, with a focus on explicating understandings of vaccine equity. COVID-19 will not be the last it is desirable to reach a consensus on what constitutes progress on equitable development, production, distribution and research.